MEKANISME PELEPASAN HORMON GONADOTROPIN (GtH-II) IKAN LELE (Clarias sp) SETELAH DI INDUKSI LASERPUNKTUR PADA TITIK REPRODUKSI - P.S.W, kusuma; Marhendra, Agung P.W.; Aulanni’am, Aulanni’am (Badan Pengkajian dan Penerapan Teknologi, 2012)
Induction laserpuncture effectively stimulates gonad maturation and spawning, but the associated gonadotropin releasing hormone (LH / GtH-II) mechanism is still unknown. So the purpose of this study demonstrate the mechanism of the release of GTH-II on catfish (Clarias sp.) after induction laserpuncture at the reproduction acupoint. The test fish consisted of 54 males and 54 females aged 8-9 months from the F1 hybrid Sangkuriang type female and Paiton type male parents. Ourstudy employed an experimental method with completely randomized design. The treatment comprised 6 levels with 9 repetitions. We were to observe gonadotropin hormone (GtH-II) concentrations pre-spawn, spawn, post-spawning in the laserpuncture exposed. As a comparison investigations were also conducted to untreated (control). Blood sampling performed at 6 h after induction laserpuncture. Hormone levels using the Elisa test kits Fish Luteinizing Hormone (LH) BIOTECH CO. CUSABIO., LTD. by Catalog No.. CSB-E15791Fh. The test results significant effect (P<0.05) increased levels of GtH-II profiles between laserpuncture inductionwith control, which profiles GTH-II levels pre-spawn conditions higher 2.2468, as well as the higher spawn condition 1,5409 in comparison with controls. However, the condition post-spawning in induction laserpuncture lower value 1.1131 compared with controls. This suggests that induction laserpuncture at the reproduction acupoint can stimulate of GABA release from GABAergic neurons pre-spawn and spawn condition. GABA stimulates the hypothalamus to release GnRH neurons. GnRH neurons stimulates the pituitary to GtH-II release. GtH-II will affect the acceleration of gonad maturation and spawning.